2022
DOI: 10.1088/1742-6596/2193/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and material characterization of calcium carbonate (CaCO3) from the waste of chicken eggshells

Abstract: Synthesis and basic characterization of calcium carbonate (CaCO3) material produced from the extraction of chicken egg shells is proposed. The studied method is applied for the basic analysis of the mineral CaCO3 in the field of membrane materials. Three basic characteristics of CaCO3 have been investigated, namely microstructure, crystal structure and vibrational modes. Microstructure were measured using a scanning electron microscope (SEM), while crystal structure were measured using an X-ray diffractometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The existence of a hydroxyl (-OH) group or an acidic hydrogen (-OH) group may be indicated by the presence of peaks 3400 and 2516 cm -1. The two peaks which were noted clearly at about 712, and 872 cm -1 , respectively indicated the presence of calcium carbonate [13,14,15]. The spectra analysis for calcite prepared from eggshell (red curve) shows an apparent peak at 711,872, 2516 cm -1 .…”
Section: X-ray Diffraction Xrd Spectrummentioning
confidence: 99%
“…The existence of a hydroxyl (-OH) group or an acidic hydrogen (-OH) group may be indicated by the presence of peaks 3400 and 2516 cm -1. The two peaks which were noted clearly at about 712, and 872 cm -1 , respectively indicated the presence of calcium carbonate [13,14,15]. The spectra analysis for calcite prepared from eggshell (red curve) shows an apparent peak at 711,872, 2516 cm -1 .…”
Section: X-ray Diffraction Xrd Spectrummentioning
confidence: 99%
“…This Si/Al ratio places the activated carbon in the category of intermediate adsorption capacity. Notably, a lower Si/Al ratio tends to render activated carbon more hydrophilic, emphasizing the interconnected relationship between elemental composition, surface properties of material, and adsorption capacity [11,16].…”
Section: B Cmentioning
confidence: 99%
“…3. The results suggested that the calcium carbonate synthesized from scallop shell waste has a spherical shape and is not uniform in size [57][58][59]. Besides, the test results also indicate the presence of agglomeration caused by several factors, such as sintering temperature, sintering time, uneven crushing, and the duration of the crushing process [58,60,61].…”
Section: Experimental Setup Cnc Milling Machiningmentioning
confidence: 99%
“…Based on the XRD results presented in Figure 6, CaCO 3 has a single phase with calcite crystal symmetry indicated by the highest peak of 1194.07 at 2θ = 29.4554 o . Meanwhile, its shape is a trigonal crystal (hexagonal axes) [57]. The Miller index for CaCO 3 synthesized from scallop's shell at 29.45, 39.45, 43.21, 47.55, and 48.57 angles are (104), ( 113), ( 202), (018), (116).…”
Section: Fig 5 Xrd Graph Of Caco 3 Nanoparticlesmentioning
confidence: 99%